2022
DOI: 10.3390/nursrep12010010
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Training Programs for Non-Health Professionals and Volunteers Working with Asylum Seekers and Refugees: A Scoping Review Protocol

Abstract: The number of people forcibly displaced worldwide is increasing. It is an imperative challenge to provide mental health training for non-health professionals and volunteers who work with those vulnerable populations. The objective is to identify mental health training programs for non-health professionals and volunteers, without mental health training, to work with asylum seekers or refugees in any context. Literature about mental health training programs for adults, non-health professionals and volunteers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This scoping review was conducted according to the JBI methodology for scoping reviews ( 29 , 30 ) , following an a priori published protocol which describes the methodological procedures used ( 24 ) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This scoping review was conducted according to the JBI methodology for scoping reviews ( 29 , 30 ) , following an a priori published protocol which describes the methodological procedures used ( 24 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Then, a full search strategy described in Chart 1 with terms adapted for each source, was carried out in the MEDLINE (EBSCO), CINAHL (EBSCO), ERIC, SCOPUS, PsycINFO, Psychology & Behavioral Sciences Collection, and in the grey literature databases The Scientific Open Access Repository of Portugal (RCAAP), and ProQuest. In the scoping review protocol ( 24 ) , the authors identified as a source of grey literature the OpenGrey database. However, OpenGrey was discontinued in 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations